2014
DOI: 10.7567/jjap.53.04ed18
|View full text |Cite
|
Sign up to set email alerts
|

Properties of crystalline In–Ga–Zn-oxide semiconductor and its transistor characteristics

Abstract: We report, in this paper, that crystalline In–Ga–Zn-oxide (IGZO) can be formed over an amorphous surface or over an uneven surface by a sputtering process at lower than 500 °C through the purification of IGZO. Crystalline IGZO, in which no clear grain boundary is observed, shows c-axis alignment but random a- and b-axis orientations without alignment. This crystal morphology differs from other morphologies that have been known thus far, such as single crystal and polycrystal morphologies. Our model for underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 28 publications
0
76
0
Order By: Relevance
“…PL was used to characterize the defects in the IGZO thin films. 14 The GaO(ZnO)m þ blocks are in wurtzite structure, but InO 2 À in a cubic structure, [21][22][23] and the crystalline IGZO are alternately stacked with InO 2 À layers and GaO(ZnO)m þ blocks. Amorphous halo peaks are observed at around 33 , and no sharp XRD peaks can be identified in the samples annealed at temperatures lower than 600 C. However, the sharp diffraction peaks of crystalline InGaZnO 4 appear when the films are annealed at 800 and 950 C. Particularly, the IGZO thin films are almost completely crystallized when annealed at 950 C for only 3 min, which is better than the samples annealed at 800 C for 1 h. Therefore, the annealing temperature rather than the annealing duration dominates the crystallization of a-IGZO thin films.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PL was used to characterize the defects in the IGZO thin films. 14 The GaO(ZnO)m þ blocks are in wurtzite structure, but InO 2 À in a cubic structure, [21][22][23] and the crystalline IGZO are alternately stacked with InO 2 À layers and GaO(ZnO)m þ blocks. Amorphous halo peaks are observed at around 33 , and no sharp XRD peaks can be identified in the samples annealed at temperatures lower than 600 C. However, the sharp diffraction peaks of crystalline InGaZnO 4 appear when the films are annealed at 800 and 950 C. Particularly, the IGZO thin films are almost completely crystallized when annealed at 950 C for only 3 min, which is better than the samples annealed at 800 C for 1 h. Therefore, the annealing temperature rather than the annealing duration dominates the crystallization of a-IGZO thin films.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, it is urgent to study the influence of thermal annealing on the structural and electronic properties of IGZO thin films. 14 In the work of this paper, IGZO thin films are fabricated by radio-frequency (rf)-magnetron sputtering and then thermal annealed both at low and high temperatures. Ide et al 10 investigated the effects of thermal annealing on the structural and optical properties of a-IGZO thin films annealed in an O 2 atmosphere at 100-800 C and in air at 1000 C. They found that crystallization at high temperature could lead to densification of thin films and the band gaps were enlarged considerably.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to thin-film a-IGZO technology's property of very low leakage [19], the cells will still keep their value on the internal node for a certain time after the supply is turned off, and can be regenerated when the supply is applied again. This effect depends on the Ids current at Vgs=0, and is therefore dependent on the exact properties of the technology.…”
Section: Technologymentioning
confidence: 99%
“…A difference in the procedures between nc-and CAAC-IGZO films is substrate temperature, i.e., room temperature for nc-IGZO films, and 300°C (which is extremely lower than the crystallization temperature) for CAAC-IGZO films. In terms of morphology, pellets are stacked randomly in nc-IGZO films, whereas they are stacked to have c-axis alignment perpendicular to the film surface in CAAC-IGZO films (7,10). Figure 3 shows a plan-view TEM image (a) and a color mapping image (b) of a CAAC-IGZO film.…”
Section: Plan-view Tem Observation Of Caac-igzo Filmmentioning
confidence: 99%